Quality of life of children with HIV/AIDS in meeting their developmental stages based on WHOQOL-100 - Jati, Armadini Caesar Ika; Imelda, Johanna Debora (Public Health Risk Assesment Journal, 2025)
Background: The number of HIV/AIDS children in Indonesia is rising, impacting their low quality of life. World Health Organization Quality of Life-100 (WHOQOL-100) is necessary to assess their life perceptions. Improving their quality of life requires a lifespan perspective to understand their development. This study aims to describe HIV/AIDS children's quality of life using WHOQOL- 100 and how it aligns with their developmental stages. Methods: This study employs a literature review method, as defined by Knopf (2006), to synthesize existing research on the quality of life of children with HIV/AIDS. It follows Neuman’s (2014) process of identifying, filtering, and analyzing relevant studies using WHOQOL-100 as a framework. The review focuses on journals from 2014-2024, selecting studies that involve children under 21, to draw broad conclusions and identify gaps in research. Findings: The findings reveal that children with HIV/AIDS have issues such as pain, poor nutrition, sleep problems, cognitive issues, low self-esteem, and caregiver burden. Early ART treatment, strategies against social stigma, good financial management, adequate healthcare access, and spiritual support are crucial for the children with HIV/AIDS. Inadequate caregiving, financial oversight, mismatched spiritual support, social stigma, and health issues hinder their development. Conclusion: Social support from caregivers and government health services play a crucial role in improving the quality of life for children with HIV/AIDS. However, not all children meet their developmental stages, highlighting the need for caregiver support, peer interactions, and consistent health services. Novelty/Originality of this Study: This study offers a unique perspective on the quality of life of HIV/AIDS-affected children in Indonesia by utilizing the WHOQOL-100 to explore how developmental stages influence their well-being, highlighting the importance of early treatment, caregiver support, and addressing social stigma in enhancing their quality of life.